Physical and Mental Workload Measurement on Warehouse Division Operators of PT.X Using Objective Workload and Subjectives Workload Assessment - Sufyan, Agi Agus Setiawan; Mulyana, Yayan; Kusumadewi, Afriani; Santang, Ilham Eka (Universitas Insan Cendekia Mandiri, 2024)
PT. X is one of the companies engaged in the Flavors and Fragrances. The role of employees as resources in work activities in the Warehouse Department is very important for the sustainability of work because almost all activities use human power, from receiving and storing, picking, packaging to loading, many still use human power and the most frequently done is the process of lifting and moving both raw materials and finished goods. The loads lifted are also diverse and in quite large quantities. Based on the results of interviews with operators, information was obtained that soreness in the waist, back and hands occurred as a result of poor work attitudes and heavy lifting loads. There are also psychological complaints experienced by the Warehouse Division due to the demands of work targets that are felt to be less relevant in each shift, causing stress and mental pressure that can affect performance and work results that are less than optimal. To determine the magnitude of the physical and mental workload of employees in the Warehouse Division, measurements were carried out using the hear rate reserve (%HR reserve) method and NASA-TLX (National Aeronautics and Space Administration Task Load Index) to see the physical and mental workload. From the measurement results, it is shown that the physical workload experienced is in the light and moderate categories ranging from 1% -43.5%, while for the mental load that has a high impact ranging from Weighted Workload (WWL).